Multilingual Training Issues and Development of Teachers’ Speaking Skills for the Special Education Purposes: Kazakhstani Case Study - Moldabekova, Sandugash K.; Dlimbetova, Gaini K.; Stukalenko, Nina M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The paper’s main purpose is to analyse approaches to the development of multilingual education and the development of speech teaching skills in the special education system. Background: Improving the special education system is challenging because it takes a long time to change. The learning process must include the possibility of educating all groups of the population. Method: During the study, the current state of the implementation of multilingual education within the framework of the Kazakhstani educational process was analysed, national and regional features of the process under study were investigated, prospects for its further improvement were considered. Results: Based on the results of the study, scientific, methodological, and theoretical foundations of the development of multilingual teacher training in a modern educational institution are summarised; educational and methodological aspects of the issue are described. Conclusion: The results obtained are of theoretical and practical importance for inclusive multilingual training of teaching staff and the improvement of teacher education in general, the implementation of leading ideas for the modernisation of all professional education.